Dinámica de los macronutrientes en palto (Persea americana Mill.) ´Hass´ bajo condiciones de la costa central peruana - Tomassini-Vidal, Luis Rodrigo (2022)
The international growing demand of the avocado (Persea americana Mill.) market, together with the expansion of its agricultural area, requires the increasing of its technification, which makes necessary to have information aboutnutrient absorption in relation to its phenology. Therefore, an experiment was conducted in a commercial avocado production field of the farm “Don Ricardo” located on the central coast of Peru, in order to characterize the dynamics of macronutrients (N, P, K, Ca and Mg). The methodology followed and the results obtained will be the main guide to improve and implement more efficient fertilization strategies that will lead to higher yields and lower production costs in this crop. The experiment included 5 production cycles, from 2014-15 to 2018-19, in 7 phenological stages, collecting according to the crop development, leaves, panicles and fruits. 40 randomized plants were selected from a total of 50 plants marked as sampling area. The results were analyzed using a descriptive statistic, with box diagrams of the concentration of each nutrient by phenological stage. Two graphs per element were generated to represent the leaf dynamic and the fruit dynamic, respectively, including the data taken from the flower. It was concluded that the highest nutrient requirements of avocado were during the flowering, the fruit set and in fruits from 10 mm to 30 mm in diameter. The most abundant form of nitrogen was nitric, and it was accumulated mainly in the productive organs. The phosphorus, potassium, calcium and magnesium concentrations decreased as the fruit grew, and calcium and magnesium concentrations in leaves were higher than in fruits.